Elvis is King! - Winter, Jonah, 1962- (Schwartz & Wade Books, 2019)
Presents the life and legacy of Elvis, from his birth in Mississippi through his music career, his time in the army, his marriage, and his induction into the Rock & Roll Hall of Fame.